State violence in Mapuche territory:: The death of Alex Lemün and the fight for justice in Chile (2002-2022) (Revista de História Regional, 2025)
This paper deals in a historical way, the murder – in a rural context – of the young Mapuche Alex Lemün, struck by police bullets in November 2022 in the province of Malleco, in the Araucanía region. His death is a reflection of sustained and systematic racist and violent state behavior against the Mapuche people and their historical demands. Theoretically, this work is articulated from the debates around racialized violence and racial hate speech, as a colonial trend not overcome by the Chilean state. Methodologically, this work is based on criticism and diversity of sources and their analysis.
Keywords: Alex Lemün - Mapuche Movement - Chilean State - Racialized violence - Impunity